Utilisation of waste Agaricus bisporus and Torreya grandis as potential natural additive coating in Agaricus bisporus preservation - Haining Zhuang; Moyao Yang; Tao Feng; Wenfeng Ding; Lingen Chen; Yongjin Qiao; Da Chen; Wei Jia; Jingsong Zhang (Czech Journal of Food Sciences, 2022)
Natural additives obtained from vegetable and fruit wastes can potentially be used as coatings to enhance the shelf life of button mushrooms (Agaricus bisporus). The present study was therefore conducted to assess the effects of natural additive coatings A. bisporus polysaccharides (ABP) and Torreya grandis essential oils (TEO) on the post-harvest quality of button mushrooms up to 16 days under cold storage (4 °C). Different concentrations for coatings were used including control (no additives), 500, 1 000, 5 000 ppm or a combination of ABP and TEO. Changes in weight loss, firmness, polyphenol oxidase (PPO) activity and microbial biomass were investigated as well as the sensory evaluation was carried out. Results show a significant decrease in the weight loss rate (decreased up to 2.34%), down regulated the PPO activities (reduced up to 30.15%) and maintained tissue firmness in ABP/TEO treatments compared to the control, whereas TEO inhibited especially the growth of microorganisms. Natural additive coatings can better protect the inner mushroom colour and flavour compared to the control.